Effect of Brewers’ Spent Grain Addition to a Fermented Form on Dough Rheological Properties from Different Triticale Flour Cultivars - Aliona Ghendov-Mosanu; Sorina Ropciuc; Adriana Dabija; Olesea Saitan; Olga Boestean; Sergiu Paiu; Iurie Rumeus; Svetlana Leatamborg; Galina Lupascu; Georgiana Gabriela Codină (Foods)
Triticale grains and brewers’ spent grain (BSG) can be new sources to develop food products. From a socio-economical point of view, this fact is important since triticale is easily adapted to the climatic changes and BSG is a low-cost material which may lead to a “zero-waste” desiderate. In this study, dough rheological properties obtained from different triticale cultivars (Ingen 33, Ingen 35, Ingen 54, and Ingen 93) cultivated in the Republic of Moldova and BSG in a fermented form (BSF) in an addition level of 10% and 17.5% were analyzed. For this purpose, different rheological devices, such as Mixolab, Alveograph, HAAKE MARS 40 Rheometer, Falling Number, and Rheofermentometer, were used. Also, the pH value of the dough samples with different levels of BSF addition during fermentation was determined. According to the data obtained, BSF addition decreased water absorption values; torques values corresponding to stages 1–5 of the Mixolab curve; and dynamic rheological elastic, viscous, and complex modules. For the 17.5% BSF addition to triticale flour, the best rheological results were obtained for the Ingen 33 and Ingen 54 varieties. In addition, the BSF addition decreased the baking strength and tenacity of the Alveograph curve. The pH values of the dough samples during fermentation significantly decreased (p < 0.05) with the increased amount of BSF incorporated into the dough recipe. The highest pH decreased values were obtained for Ingen 35 with a 17.5% BSF addition, which varied between 5.58 and 5.48. During fermentation, all data recorded by the Rheofermentometer device were improved. The dough samples presented a high retention coefficient, which varied between 99.1 and 99.5%. The falling number decreased with the increasing level of BSF in triticale flour, indicating an increase in α-amylase activity in the mixed flours. The principal component analysis data showed a strong association between triticale flour varieties without a BSF addition and those with a high amount of BSF incorporated into the dough recipe. The results obtained indicate the fact that many mixes between BSF and different triticale varieties may lead to bakery products of a good quality.